Identification of TMPRSS3 as a Significant Contributor to Autosomal Recessive Hearing Loss in the Chinese Population - Xue Gao; Sha-Sha Huang; Yong-Yi Yuan; Jin-Cao Xu; Ping Gu; Dan Bai; Dong-Yang Kang; Ming-Yu Han; Guo-Jian Wang; Mei-Guang Zhang; Jia Li; Pu Dai (Neural Plasticity)
Hereditary hearing loss is characterized by a high degree of genetic heterogeneity. Mutations in the TMPRSS3 (transmembrane protease, serine 3) gene cause prelingual (DFNB10) or postlingual (DFNB8) deafness. In our previous study, three pathogenic mutations in TMPRSS3 were identified in one Chinese family. To evaluate the importance of TMPRSS3 mutations in recessive deafness among the Chinese, we screened 150 autosomal recessive nonsyndromic hearing loss (ARNSHL) families and identified 6 that carried seven causative TMPRSS3 mutations, including five novel mutations (c.809T>A, c.1151T>G, c.1204G>A, c.1244T>C, and c.1250G>A) and two previously reported mutations (c.323-6G>A and c.916G>A). Each of the five novel mutations was classified as severe, by both age of onset and severity of hearing loss. Together with our previous study, six families were found to share one pathogenic mutation (c.916G>A, p.Ala306Thr). To determine whether this mutation arose from a common ancestor, we analyzed six short tandem repeat (STR) markers spanning the TMPRSS3 gene. In four families, we observed linkage disequilibrium between p.Ala306Thr and STR markers. Our results indicate that mutations in TMPRSS3 account for about 4.6% (7/151) of Chinese ARNSHL cases lacking mutations in SLC26A4 or GJB2 and that the recurrent TMPRSS3 mutation p.Ala306Thr is likely to be a founder mutation.